Comparative Study of AMMI- and BLUP-Based Simultaneous Selection for Grain Yield and Stability of Finger Millet [Eleusine coracana (L.) Gaertn.] Genotypes - Anuradha, N.; Patro, T. S. S. K.; Singamsetti, Ashok; Sandhya Rani, Y.; Triveni, U.; Nirmala Kumari, A.; Govanakoppa, Nagappa; Lakshmi Pathy, T.; Tonapi, Vilas A. (Frontiers in Plant Science, 2022)
Finger millet, an orphan crop, possesses immense potential in mitigating climate change and could offer three-fold security in terms of food, fodder, and nutrition. It is mostly cultivated as a subsistence crop in the marginal areas of plains and hills. Considering the changes in climate inclusive of recurrent weather vagaries witnessed every year, it is crucial to select stable, high-yielding, area-specific, finger millet cultivars. Sixty finger millet varieties released across the country were evaluated over six consecutive rainy seasons from 2011 to 2016 at the Agricultural Research Station, Vizianagaram. The genotype × environment interaction (GEI) was found to be significant in the combined ANOVA. Further, AMMI analysis asserted that genotypes and the GEI effects accounted for approximately 89 percent of the total variation. Strong positive associations were observed in an estimated set of eleven stability parameters that can be chosen to identify stable genotypes. Further, non-parametric and parametric simultaneous selection indexes (NP-SSI & P-SSI) were calculated utilizing AMMI-based stability parameter (ASTAB), modified AMMI stability value (MASV) and Modified AMMI stability index (MASI) to identify stable high yielders. Both methods had inherent difficulties in ranking genotypes for SSI. To overcome this, the initial culling (C-SSI) of genotypes was introduced for stability. In the C-SSI method, the top ten genotypes were above-average yielders, while those with below-average yield were observed in NP-SSI and P-SSI methods. Similarly, estimation of Best Linear Unbiased Prediction (BLUP) based simultaneous selections like Harmonic Mean of Genotypic Values (HMGV), Relative Performance of Genotypic Values (RPGV), and Harmonic Mean of Relative Performance of Genotypic Values (HMRPGV) revealed that none of the top ten entries were below-average yield. The study has proven that C-SSI and BLUP-based methods were equally worthy in the selection of high-yielding genotypes with stable performance. However, the C-SSI approach could be the best method to ensure that genotypes with a considerable amount of stability were selected. The multi-year trial SSI revealed that entries Indaf-9, Sri Chaitanya, PR-202 and A-404 were ascertained to be the most stable high-yielding (>3000 kg/ha) genotypes among medium to late duration while VL324 and VL146 among early entries.